Intensification of food production systems: A boon or a bane? - Kennady, Vijayalakshmy; Chakraborty, Sharmistha; Biswal, Jyotsnarani; Rahman, Habibar (2023)
Food production systems are intensified because of various acts taken by people on an individual, community, or organisational level. The need for intensification in the form of greater output is most pressing when the food supply needs to be increased, such as during periods of high population growth. When social or environmental problems are involved, intensification that uses resources more effectively may be more important. In either case, changes brought about by intensification should be cognitively understood as opposed to extensive modifications, which involve either a rise or fall in the number of inputs utilised. The necessity of sustainable intensification of food production systems is emphasised in this assessment, along with its benefits and drawbacks.